Measuring land rental market participation in smallholder agriculture can survey design innovations improve land market participation statistics? - Abate, Gashaw T.; Abay, Kibrom A.; Chamberlin, Jordan; Sebsibie, Samuel (International Food Policy Research Institute, 2024)
The emergence of rural land rental markets in Sub-Saharan Africa is recognized as a key component of the region’s ongoing economic transformation. However, the evidence base on land market participation relies on survey-derived measures, which do not always cohere when compared and triangulated, suggesting the possibility of non-trivial measurement error. We report the results of a priming and list experiments designed to shed light on a persistent mystery in rural household survey data from Africa: why there are so many fewer self-reported landlords (renters-out) than tenants (renters-in)? Our design addresses two hypotheses using experimental data from Ethiopia. First, rented-out and rented-in land may be systematically underreported because enumerators and respondents are typically primed to emphasize parcels that are actively managed/cultivated by the household. Second, rented or sharecropped-out land may be systematically underreported because of respondents’ reluctance to acknowledge an activity for which public disclosure may have negative repercussions. We address the first hypothesis with a priming experiment by exposing a random subset of respondents to a nudge that explicitly reminded them to fully account for all land, including rented/sharecropped-in and rented/sharecropped-out. We address the second hypothesis with a double-list experiment, designed to elicit true rates of land renting and sharecropping-out. We find that nudging induces about 4 percentage points increase (or 13% in relative terms) in the share of households participating in renting in or sharecropping-in practices but has negligible effects on reported rates of renting and sharecropping-out. Interestingly, our list experiment indicates much higher revealed rates of renting-out (14-15%) than is reflected in the nominal parcel-roster responses (3%). The magnitude of the latter finding fully explains the apparent difference in renting in versus renting-out rates derived from the regular parcel roster responses. These results indicate that efforts to document land market participation rate and associated impacts must overcome large systematic reporting biases.